The Reproducibility of Trophectoderm Biopsies in Euploid, Aneuploid, and Mosaic Embryos Using Independently Verified Next-Generation Sequencing (NGS): A Pilot Study. Issue 8 (August 2021) - Sachdev, Nidhee M.; McCulloh, David H.; Kramer, Yael; Keefe, David; Grifo, James A.
Abstract : (Abstracted from J Assist Reprod Genet 2020;37:559–571) Aneuploidy represents the major cause of implantation failure and miscarriage. Preimplantation genetic testing (PGT-A) was developed to select euploid embryos for transfer and improve pregnancy rate.